2013
DOI: 10.46429/jaupr.v97i1-2.3044
|View full text |Cite
|
Sign up to set email alerts
|

Liberación De Los Patrones De Cítricas 'Swingle Citrumelo', 'Carrizo' Y HRS 812 Para Puerto Rico

Abstract: LIBERACIÓN DE LOS PATRONES DE CÍTRICAS 'SWINGLE CITRUMELO', 'CARRIZO' Y HRS 812 PARA PUERTO RICO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Meanwhile, sweet orange cv. 'Hamlin' grafted onto 'Swingle' showed an average canopy volume of 18.02 cubic meters per tree for five-year-old irrigated trees (Román-Pérez and González, 2013). Tirado-Corbalá et al (2020) reported an average canopy volume of 7.74 and 8.01 cubic meter per tree for cv.…”
Section: Tree Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, sweet orange cv. 'Hamlin' grafted onto 'Swingle' showed an average canopy volume of 18.02 cubic meters per tree for five-year-old irrigated trees (Román-Pérez and González, 2013). Tirado-Corbalá et al (2020) reported an average canopy volume of 7.74 and 8.01 cubic meter per tree for cv.…”
Section: Tree Growthmentioning
confidence: 99%
“…It is an interspecific hybrid (Poncirus x Citrus) tolerant to several diseases. In 2013, the Agricultural Experiment Station (AES) of the University 132Román-Paoli et al/oRange micRoiRRigation of Puerto Rico (UPR) recommended the use of 'Swingle citrumelo' as a rootstock after having studied the cultivar for several years and in several locations (Román-Pérez and González, 2013).…”
Section: Introductionmentioning
confidence: 99%